Correlation between polymorphisms in IGF2/H19 gene locus and epithelial ovarian cancer risk in Chinese population - Zhang, Hai-Bo; Zeng, Ying; Li, Tai-Lin; Wang, Guo (Genomics (San Diego, Calif.), 2020)
To investigate the association between SNPs in human IGF2/H19 gene locus and epithelial ovarian cancer (EOC) risk, we performed a case-control study in 422 individuals (219 EOC patients and 203 cancer-free controls). Four SNPs (rs2525885, rs2839698, rs3741206, rs3741219) were found to be related with EOC risk. Specifically, the minor allele C of rs2525885 and allele A of rs2839698 was associated with elevated EOC genetic susceptibility under both dominant and recessive models (TC + CC vs TT: adjusted OR: 1.61, P = .031; CC vs TT + TC: adjusted OR: 4.87, P = .014; GA + AA vs GG: adjusted OR: 1.63, P = .023; AA vs GG + GA: adjusted OR: 2.43, P = .007). For rs3741206, the genotype TC + CC was associated with a significant decrease in EOC risk with the TT genotype as reference in a dominant genetic model (adjusted OR: 0.44, P = .003), while for rs3741219, genotype AA was associated with a 59% decrease in EOC risk only in the recessive model (adjusted OR: 0.41, P = .038). In the stratified analysis, an increased risk associated with the variant genotypes was observed in only subjects aged >47 years for rs2525885 (adjusted OR = 2.04, P = .024), rs2839698 (adjusted OR = 2.50, P = .047) and rs3741206 (adjusted OR = 0.37, P = .009), respectively. What's more, the TC + CC genotype of rs2525885 was significantly associated with advanced FIGO stage (III vs II, adjusted OR = 2.73, P = .040). •A case-control study in 422 individuals was performed to find susceptibility SNPs in IGF2/H19 gene locus underlying EOC.•Four SNPs (rs2525885, rs2839698, rs3741206, rs3741219) were firstly found to be related with epithelial ovarian cancer risk.•For rs2525885 and rs2839698, an increased risk associated with the variant genotypes was observed in subjects aged >47 years.•A decreased risk associated with the variant genotypes was observed in only subjects aged >47 years for rs3741206.•TC+CC genotype of rs2525885 was significantly associated with advanced FIGO stage.